Is AI Reducing Healthcare Spending? An Academic Analysis of Digital Health Economics - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Is AI Reducing Healthcare Spending? An Academic Analysis of Digital Health Economics Introduction: The Promise and the Price Tag of AI in Healthcare The...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation